2006
DOI: 10.1007/s00330-006-0444-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of focal liver lesions: comparative study of contrast-enhanced ultrasound versus spiral computed tomography

Abstract: The purpose of this study was to compare the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) with spiral computed tomography (SCT) for the characterization of focal liver lesions (FLL) and to determine the degree of correlation between the two techniques. Seventy-seven FLL (45 hepatocellular carcinomas; 12 metastases; ten hemangiomas; two regenerating/dysplastic nodules; eight focal nodular hyperplasias) detected with ultrasound (US) were prospectively evaluated by CEUS using a second-generation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…The enhancement patterns of the lesion are evaluated in three vascular phases (the hepatic arterial, portal venous and late phases), where the hepatic arterial phase provides information on the degree and pattern of vascularity and the portal venous and late phases provide important information on the differention between benign and malignant liver lesions [1]. A previous study has shown that CEUS using SonoVue® (Bracco, Milan, Italy) and spiral-CT provides similar diagnostic accuracy in the characterisation of focal liver lesions [2].…”
Section: Advances In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement patterns of the lesion are evaluated in three vascular phases (the hepatic arterial, portal venous and late phases), where the hepatic arterial phase provides information on the degree and pattern of vascularity and the portal venous and late phases provide important information on the differention between benign and malignant liver lesions [1]. A previous study has shown that CEUS using SonoVue® (Bracco, Milan, Italy) and spiral-CT provides similar diagnostic accuracy in the characterisation of focal liver lesions [2].…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Most malignant tumours show predominantly microbubble washout, while benign tumours show persistent microbubble uptake on CEUS with a low-mechanical-index mode and a sulphur hexafluoride-filled microbubble contrast agent [1,2,5]. Despite this, enhancement in the late phase provides important information about the nature of the lesion.…”
Section: Quantitative Analysis Of Ceus In Fnh and Hccmentioning
confidence: 99%
“…CEUS significantly improved the diagnostic performance in small FLLs compared to BUS [8] . Several other studies also provided evidence that CEUS has sensitivity and specificity similar to computed tomography (CT) and magnetic resonance imaging (MRI) in terms of detection and characterization of FLLs [9][10][11][12] . In this article, the application of CEUS for the detection of different benign and malignant FLLs in liver cirrhosis will be described and discussed on the basis of our experience and latest literature data.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies have shown that contrast-enhanced ultrasound, computer tomography (CT), and magnetic resonance imaging (MRI) have the same sensitivity and specificity for screening and identifying small liver nodules [7][8][9]. It is generally believed that most of DNs are enhanced synchronically with the surrounding liver parenchyma [10].…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%